2015
DOI: 10.18632/oncotarget.4714
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine cathepsin activity suppresses osteoclastogenesis of myeloid-derived suppressor cells in breast cancer

Abstract: Cysteine cathepsin proteases contribute to many normal cellular functions, and their aberrant activity within various cell types can contribute to many diseases, including breast cancer. It is now well accepted that cathepsin proteases have numerous cell-specific functions within the tumor microenvironment that function to promote tumor growth and invasion, such that they may be valid targets for anti-metastatic therapeutic approaches. Using activity-based probes, we have examined the activity and expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…The protocol followed was as previously described . Specifically, for cathepsin B activity gels, activity‐based probes [GB123 (1 μ m ) [28] or BMV109 (0.1 μ m ) ] were added to lysates from a 100× stock, and proteins were incubated for 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol followed was as previously described . Specifically, for cathepsin B activity gels, activity‐based probes [GB123 (1 μ m ) [28] or BMV109 (0.1 μ m ) ] were added to lysates from a 100× stock, and proteins were incubated for 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The canonical model describing this process entails secretion of tumor-derived factors, especially receptor activator of nuclear factor kappa-B ligand), which stimulates activation of osteoclast precursors to mature osteoclast, which then resorb bone, leading to the release of protumorigenic growth factors and formation of a niche conducive of tumor growth [19][20][21]. Previously, we and others have shown that myeloid-derived suppressor cells (MDSC) function as a direct source of osteoclasts [22][23][24]. An important finding in our studies was only MDSC within the bone TME differentiated into osteoclast, whereas MDSC from nonbone sites of BCa metastasis or from spleen did not [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that the inhibition of cathepsin by agents such as CA074 (CatB inhbitor) and JMP-OEt (pan cathepsin inhibitor) leads to an increase in osteoclastogenesis, osteoclast surface area, and average cell size [95,96]. This suggests that cathepsin inhibition may increase the proliferation rates of precursor cells, thereby increasing the number of fusion events or the rate of osteoclast fusion.…”
Section: Role Of Cathepsins In Bone Remodelingmentioning
confidence: 99%